Perbedaan Rasio Trombosit Limfosit Pre dan Post Terapi Kemoradiasi Kanker Serviks di Rumah Sakit Pusat Angkatan Laut dr. Ramelan Surabaya - Marbentan, Purwo Diva Nadib; Sudiarta, Ketut Edy; Purwaningsari, Diah; Puspita, Angela (Jurnal Kedokteran Meditek, 2025)
Introduction: Cervical cancer is caused by persistent infection with HPV transmitted through sexual intercourse. Chemoradiation is often used in the treatment of cervical cancer because it can reduce recurrence and further cell growth and can increase survival. Increased Platelet Lymphocyte Ratio (RTL) can be used to track the progression of cervical cancer and the degree of differentiation of cancer cells. High RTL indicates a worse degree of cell differentiation and vice versa. Purpose: The aim of this study was to determine the difference in RTL in cervical cancer patients pre and post chemoradiation therapy. Methods: The research design is cross-sectional with total sampling. Data was taken from medical records of cervical cancer patients at the Department of Obstetrics and Gynaecology, RSPAL dr. Ramelan Surabaya in year 2000 - 2023. Results: The average RTL for cervical cancer patients before chemoradiation was 193.1293; and after chemoradiation 169.5459. The results of the Wilcoxon signed rank test showed a significant decrease (p < 0.001). This research proves that there is a significant difference in the Platelet Lymphocyte Ratio (RTL) of stage ≥ IIB cervical cancer patients pre- and post-chemoradiation therapy. Statistical tests show significant results. Conclusion: Chemoradiation has been proven to significantly reduce RTL, and it can be concluded that giving chemoradiation to cervical cancer stage IIIB and above provides good results.